Resilience and self concept of competence in institutionalized and non institutionalized young people - Martins,Maria Helena Venâncio (2016)
The institutionalization of young people may have important negative influence on their development and emotional well being. The aim of this study was to analyze the relations between resilience and the self concept of competence in institutionalized and non institutionalized young people. The sample was composed of 158 young people, aged between 15 and 18 years old. The following instruments were used: a socio-demographic questionnaire, the Healthy Kids Resilience Assessment Module and the Self Concept of Competence Scale. The results showed: (1) no significant differences between the two groups in terms of resilience; (2) the non institutionalized sample revealed higher scores on the self concept competence; and (3) there was a strong positive correlation between resilience and self concept of competence amongst the institutionalized sample. These results are discussed in the light of the constructivist perspective of resilience.